Distribution as a modern form of marketing structures in tourism - Basyuk, Daria; Antonenko, Irina; Muzychka, Yelyzaveta (My University, 2017)
The article focuses on the development of theoretical and methodological approaches, practical recommendations on management of distribution activities of tourism enterprises. It is determined that the construction of an effective distribution system for tourism services should be carried out on the basis of their sales potential, channels for the promotion of tourism products (direct, indirect) and the formation of strategies. The usage of electronic distribution in tourism is considered.
Keywords: дистрибуція; збут туристичних продуктів (послуг); туристичний продукт; туроператор; турагент; дистрибуция; сбыт туристических продуктов; туристический продукт; distribution; marketing of tourism goods (services); tourism product; tour operator; travel agent; кафедра туристичного та готельного бізнесу